Variasi Morfometrik Tetragonula laeviceps di Berbagai Habitat di Provinsi Sulawesi Tengah - I Made Budiarsa; Fatmah Dhafir; Manap Trianto (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: Habitat is a place for living things to grow and develop. Differences in habitat in an area can affect the size of an organism. This study aims to determine the morphometric variations of Tetragonula laeviceps found in urban and forest habitats in Central Sulawesi Province. Methods: This research was conducted with roaming technique. Morphometric characters observed were 35 characters of stingless bee and analyzed using Microsoft Excel software. Results: The results of this study indicated that the morphometric size variation of T. laeviceps found in forest habitats (3.58 mm) is greater than that of wild bee in urban habitats (3.05 mm). Conclusions: Different habitat characteristics can affect the morphometry variations of the bee, especially in T. laeviceps species. The bee's morphometry body size is greater than in the forest habitat, because in that habitat there are environmental temperatures and types of plant sources of nectar which are more supportive for bee life compared to urban habitats.